The Effects of Air Pollution on Socio – Economic Activities in Sokoto State, Nigeria - Bello Muhammad, Muhammad; Abdul Aziz, Rahimah; W.C. Yew, Vivien (International Journal of Engineering and Technology, 2018)
The main aim of the paper is to look into the effects of air pollution on socio – economic activities in Sokoto state, Nigeria, to sensitize the populace on the dangers associated with environmental pollution and possibly profer solutions to the problems. Secondary data was used to systematically review the literature through narrative method. Talcott Parsons ‘AGIL’ schema was used in this paper. The findings revealed some pollutants that were identified and widely associated with air pollution, especially with emissions from industrial activities, auto mobiles and other sources of pollutants that causes harm to both man and his environment. The findings also revealed that Sokoto Cement Company is supposed to be a source of development to Kalambaina community, through job creation, providing cheaper building materials and other social amenities, however, it has negatively impacted the community to a large extent by endangering the health of the populace, thereby, stagnating their socio-economic development. Recommendations were made that the government should create policies that will make the Company responsible for the damages caused by pollution to the host community.They should provide tenure employment, social amenities and also be made to implement environment friendly policies that will limit the pollution caused by the activities of the Company.
Keywords: Air pollution; Pollutants; Environment; Socio – economic activities; Nigeria.